2019
DOI: 10.1021/acs.joc.9b01733
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidative Cross-Coupling of Substituted Acrylamides with Alkenes Catalyzed by an Electron-Deficient CpRhIII Complex

Abstract: It has been established that an electrondeficient CpRh III complex, bearing two ester moieties on the Cp ring, [Cp E Rh III ], catalyzes the aerobic oxidative cross coupling of substituted acrylamides with both activated and unactivated alkenes, leading to (2Z,4E)-dienamides, at relatively low temperature (80 °C). Importantly, tertiary, secondary, and primary amide directing groups could equally be used in this catalysis. The mechanistic studies revealed that the electron-deficient nature of the Cp E Rh III co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…The reaction of the known 3-H-3-Cl-3,3-(PPh 3 ) 2 -closo-3,1,2-RuC 2 B 9 H 11 (1) with the corresponding tridentate nitrogen-based ligands obtained from picolylamine in benzene at 60 °C resulted in the formation of the novel ruthenacarboranes 2-6 with moderate yields (Scheme 1). The possible mechanism of the process involves the exchange of two PPh 3 ligands by two arms of nitrogen-based ligand typical for 1, following by the elimination of HCl and coordination of the third arm of the ligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of the known 3-H-3-Cl-3,3-(PPh 3 ) 2 -closo-3,1,2-RuC 2 B 9 H 11 (1) with the corresponding tridentate nitrogen-based ligands obtained from picolylamine in benzene at 60 °C resulted in the formation of the novel ruthenacarboranes 2-6 with moderate yields (Scheme 1). The possible mechanism of the process involves the exchange of two PPh 3 ligands by two arms of nitrogen-based ligand typical for 1, following by the elimination of HCl and coordination of the third arm of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…for RuC 14 B 9 H 24 N 3 : C, 38.9; H, 5.6; N, 9.7). IR: v max = 2507 cm À 1 , NMR ((CD 3 ) 2 SO, 400 MHz), 1…”
Section: Methodsunclassified
See 1 more Smart Citation
“…In 2019, Tanaka, Shibata and co-workers disclosed the aerobic cross-coupling between two vinyl alkenes using an electron-deficient CpRh( iii ) complex in which the cyclopentadienyl ring bears ester moieties (Scheme 3). 15 This strategy enabled the synthesis of (2 Z ,4 E )-configured dynamite derivatives. The catalytic turnover-limiting step ( i.e.…”
Section: Cross-dehydrogenative Coupling Of Alkenesmentioning
confidence: 99%
“…3 Besides, the change of the electronic properties of Cp ligands, particularly the electron-deficient Cp ligands, leads to a high-level catalytic efficiency. 4,5,6 For instance, Tanaka and co-workers developed a bis(ethoxylcarbonyl)-substituted cyclopentadienyl Rh catalyst (Cp E Rh( iii ), 4 b,c which affords higher yields of annulation products than the Rh catalyst with an electron-rich Cp* ligand (Scheme 1). Rovis and others reported that the Rh catalyst supported by Cp* CF3 shows higher reactivity and regioselectivity in a few types of annulation and coupling reactions.…”
Section: Introductionmentioning
confidence: 99%